Historical aspects in pain management in palliative care in an oncological reference unit - Carolina Fraga Paiva; Tânia Cristina Franco Santos; Pacita Geovana Gama de Sousa Aperibense; Gizele da Conceição Soares Martins; Lilian Dias Ennes; Antonio José de Almeida Filho
ABSTRACT Objective: Describe the actions implemented for pain management in palliative care oncology and analyze the contribution of Hospital do Câncer IV, as a reference unit at the National Cancer Institute. Methods: Study of the history of the present time, whose sources were written documents and interviews with five participants. The collection took place from February to June 2018. The analysis of the written sources took place through internal and external criticism of the documents, considering their chronology and theme. Results: Professionals contributed with actions for pain management in palliative oncology care: in discussions and final drafting of ordinances, as rapporteurs at national and international events, in the elaboration of humanization conducts and systematization of assistance in addressing pain. Final considerations: These actions favored assistance in palliative oncology care at various levels of health care for patients and families, with greater technical and scientific recognition for all.